Interactive Marketing Measurement According To Sustainable Competitive Advantage Goals: A Scale Development - Salman Neamah, Rusul; Mohammadifar, Yousef; Naderi, Nader; Rezaee, Bijan (Journal of Economics and Administrative Sciences, 2024)
Purpose: The objective of this study is to create an interactive marketing model that aligns with the commercial development strategies of mobile phone operators in Iraq.Theoretical framework: Recent literature has reported good results on the new design of the interactive marketing model that is compatible with the development of work in the Iraqi mobile phone companies in the research sample.Design/methodology/approach: Mobile phone companies in Iraq (Asia Cell, Zain, Korek) were chosen as a field for the application, and a purposive research sample consisting of (35) people was chosen from the human resources of the aforementioned companies. Questions prepared for this purpose were adopted as a tool for obtaining data, while the (Atlas-ti) program was used. Statistician in entering and analyzing research data.Findings: The volume of research has been increasing over the past 20 years, although there are only a few reference authors, institutions and journals contributing to the unification of topics. The researchers were able to design an interactive marketing model that simulates the environment and reality of mobile phone companies in Iraq.Research, Practical & Social implications: We suggest a future research agenda by highlighting the contributions made to designing marketing models to suit the environment in which companies of various types operate.Originality/value: Originality/value: The results indicated a proposal for a new interactive marketing model through which we hope to contribute to adding marketing services to companies operating in the Iraqi telecommunications sector.